Recursos no verbales en la comunicación - Rubio Ramos, William Henry (2019)
The theme nonverbal resources in communication (They are forms of communication not spoken and which messages can be communicated in through gestures, body language, posture, facial expressions, etc.). It will be developed with students from first grade of secondary education, as a way to communicate through days with people, as an essential part of the communication system and the vehicle of many fundamental human transactions that verbal communication. Even they can not just communicate. It is important because it is a fundamental element and social life, family and work. Students establish an effective and understandable type of language. To generate a general a nonverbal communication it is used nonverbal resources as sounds, images, colors, shapes, graphics, physical appearance, noise, etc.